BASED INTERNET NETWORK DESIGN VSAT KU-BAND AT JANGGA DOLOK VILLAGE OFFICE - Akhyar Lubis; Rio Septian Hardinata; Muhammad Seger (International Forum of Researchers and Lecturers, 2022)
The number of islands and the size of Indonesia's territory is a problems in building telecommunications infrastructure. VSAT satellite technology is a solution and is useful when terrestrial relations experience issues. This is because not all regions are terrestrial and can reach all islands and mainland in Indonesia. In this study, the Ku-Band VSAT was used, and the Ku-Band VSAT installation location was in Jangga Dolok Village, Lumban Julu District, Toba Samosir Regency, North Sumatra Province. The research method involves needs analysis, design, implementation, and testing. The results showed that the quality of the network obtained showed a bandwidth of 024 Kbps, 637 ms delay, 0% packet loss, 1.84 Mbit/s download throughput, and 319.18 Kbit/s uploads. The measurement analysis results in the field show that the IP Config VSAT IP can be connected to the gateway, and the connection test shows the reply response. The transmission parameter output IDU downlink SQF is 168, and the uplink is 16 Apsk 1024 K 9/10, the upload, and download measurement results show the upload results of 1.8 Mbps and 0.3 Mbps upload. All the analysis results were carried out, and it showed promising results, and the VSAT-based internet network in Jangga Dolok village was feasible to use. Keywords: VSAT Ku-Band, Topology, satellite internet.